2020
DOI: 10.3390/d12040142
|View full text |Cite
|
Sign up to set email alerts
|

Modern Benthic Foraminiferal Diversity: An Initial Insight into the Total Foraminiferal Diversity along the Kuwait Coastal Water

Abstract: Kuwait territorial water hosts an important part of national biodiversity (i.e., zooplankton and phytoplankton), but very limited information exists on the overall diversity of benthic foraminifera. On the basis of the integration of publications, reports and theses with new available data from the Kuwait Bay and the northern islands, this study infers the total benthic foraminiferal diversity within Kuwait territorial water. This new literature survey documents the presence of 451 species belonging to 156 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…This created the Gomphotherium Landbridge, thus connecting Africa with Eurasia (Rögl 1999). Al-Enezi et al (2020) recently reported the genus Olgita from the coastal zone of Kuwait, the geographically closest, documented occurrence of this taxa to our sampling point. Therefore, our findings of the O. pacifica in the studies samples together with the existing palaeoceanographic data suggest the early Burdigalian age as a possible migration time of the species into the area of the Central Iranian Basin (Fig.…”
Section: Paleoceanographysupporting
confidence: 61%
“…This created the Gomphotherium Landbridge, thus connecting Africa with Eurasia (Rögl 1999). Al-Enezi et al (2020) recently reported the genus Olgita from the coastal zone of Kuwait, the geographically closest, documented occurrence of this taxa to our sampling point. Therefore, our findings of the O. pacifica in the studies samples together with the existing palaeoceanographic data suggest the early Burdigalian age as a possible migration time of the species into the area of the Central Iranian Basin (Fig.…”
Section: Paleoceanographysupporting
confidence: 61%
“…The detection of trace elements in the sediments of Kuwait Bay suggests potential threats to marine fauna from contamination sources such as industries, desalination, power plants, and the influx from the Shatt Al-Arab. The sediment analysis plays a pivotal role in assessing environmental quality within the bay [1]. Trace metals were found in all sediment samples at concentrations below toxic effect thresholds (TET), indicating current contamination levels are low.…”
Section: Discussionmentioning
confidence: 99%
“…The country shares borders with Iraq to the north and northwest, the Arabian Gulf to the east, and the Kingdom of Saudi Arabia to the south and southwest. Spanning an area of approximately 17,818 km 2 , Kuwait's coastline stretches about 500 km, accounting for a significant portion of its territorial waters [1]. The region is characterized by a hyper-arid climate, with long summers and short winters.…”
Section: Introductionmentioning
confidence: 99%
“…Foraminifera may become a consistent part of meiobenthic communities in marine and transitional environments [22]. Al-Enezi et al [23] document for the first time the biodiversity pattern of benthic foraminifera from Kuwait Bay and the northern islands in this area.…”
mentioning
confidence: 99%